Evaluación de las canteras de la provincia de San Martín para su utilización en obras civiles - Mosquera Mendoza, Erick Javier (2011)
The province of San Martin, Tarapoto specifically its capital, is getting in recent years a major population and economic growth, and this in turn creates an increase in the construction sector, these same concerning public and private infrastructure. That is why the need to obtain the best quality building materials, in this case primarily the aggregates used in the manufacture of concrete. This thesis evaluates the different quarries in the province of San Martin and while the quality of the aggregate you get from these, for use in concrete for constructive purposes, assessing their physical and mechanical properties thereof. In Chapter 1 (Introduction), mention of the generalities of the investigation, preliminary exploration and general aspects of research-oriented study is done. Chapter 11 (Theoretical Framework), exposes the fundamental theoretical basis on which this research is based. As they are the background, objectives, justification, the conceptual framework itself and the hypothesis to prove. Within the conceptual framework theoretical background, terminology and basic concepts of research develops. Chapter 111 (Materials and Methods) contains detailed materials and methodologies used for the development of research. The materials comprising human resources and materials. equipment used, plus the methodology includes sampling, variables, and designs for the investigation itself. Chapter IV (Results), presented briefly and concisely the results obtained during the investigation, these marginalized themselves are presented without comments and / or conclusions regarding these mismos.El Chapter V (Analysis and Discussion of Results), exposes the analysis and discussion of the results presented above, because these have a selection of alternatives and testing of the hypothesis which would guide the findings. Chapter VI (Conclusions and Recommendations}, referred to in concrete and coherent conclusions and recommendations obtained in the analysis of the previous chapters form. Chapter VII (Literature), contains in summary the literature used in the preparation of this research, taking into account information about the author, publisher, edition, country, year, etc. Chapter Vlll (Annexes) Annexes, have auxiliary information, consultation and complementary that has been used in the pres ~ nte thesis. Laboratory data where the characteristics of the aggregates obtained are presented. referential and nomograms drawings, photographic panel, tables used for the preparation of this research are also presented....